Religion and public order in modern nation-states: institutional varieties and contemporary transformations - Koenig, Matthias (Religion in the public sphere: a comparative analysis of German, Israeli, American and International law, 2007)
The political significance of religion is back on the agenda of interdisciplinary academic debate. One does not need to recall the world-wide rise of Christian, Jewish and Islamic fundamentalism, the intensification of religious nationalism in South Asia, and the dynamics of religiously legitimated ethnic conflict to find evidence that religion continues to be strongly influential in modern society. Even within many seemingly “secularized” Western countries, new forms of politics of religious recognition have emerged which merit closer academic attention. It is indeed hard to find a country which is not witnessing public debates over religious symbols (headscarves, crucifixes etc.), constitutional conflicts over Church-State relations and political controversies over the accommodation of religious minorities.